(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: Newspaper style is a distinctive form of writing designed to convey information clearly, concisely, and engagingly to a broad audience. This article elaborates on the key characteristics of newspaper style, including its emphasis on clarity and simplicity, objectivity and neutrality, conciseness, and the strategic use of headlines, subheadings, idioms, colloquialisms, and cultural references. It further discusses the role of active and passive voice and reporting verbs. The article highlights the critical importance of preserving these stylistic features during translation to maintain the integrity, impact, and cultural relevance of the original text, especially when translating from English to Uzbek. Understanding and skillfully navigating these linguistic and cultural nuances are essential for translators to effectively bridge communication gaps in journalistic contexts.